Exploring socio-demographic determinants of obesity in Jordanian women of reproductive age: insights from a nationwide survey - Mahmoud Shaaban Abdelgalil; Sara Hosny El-Farargy; Mohamed Adel Dowidar; Mohamed Abd-ElGawad (BMC Public Health)
Abstract Background In Jordan, obesity has emerged as a significant public health concern, particularly among females, with a prevalence of 43.1%. This rising trend, exacerbates the burden of non-communicable diseases and places increasing strain on the healthcare system. Aim We aimed to explore the predictors associated with obesity among adult ever-married Jordanian women aged 20–49 years based on the Jordanian Population and Family Health Survey (JPFHS). Method Our study analyzed data from the JPFHS conducted in 2017-18, which initially included 14,689 ever-married women. We performed multivariable analyses to determine the socio-demographic predictors of obesity among these women. Result We included 4,339 Jordanian women in our study, of whom 2,189 were classified as obese and 2,150 had a normal body mass index (BMI). Multivariable analysis indicated that increasing age and living in Tafilahwere significantly associated with higher odds of developing obesity (p < 0.05). Conversely, factors such as being in the wealthiest category, residing in Ma’an and Aqaba, and smoking every day were significantly linked to reduced odds of obesity (p < 0.05). Additionally, no significant associations were found between obesity development and variables such as the type of place of residence, educational level, frequency of reading newspapers or magazines, radio listening, television watching, or internet use in the past month (p > 0.05). Conclusion Appropriate and targeted interventions should be developed for Jordanian women to address obesity and its related health issues. Policymakers should adopt a multilevel approach that focuses on high-risk subgroups, including older women, and those living in Tafilh. Efforts should be made to raise awareness and provide preventative measures tailored to these groups to effectively reduce obesity and its associated complications.